Influence of high-permittivity barriers on PD activity in three-layer dielectrics; Journal of Physics D: Applied Physics; Vol. 37, iss. 22 - Lebedev S. M. Sergey Mikhailovich; Gefle O. S.; Pokholkov Y. P. Yuri Petrovich; Gockenbach E.; Borsi H.; Wasserberg V.; Abedi V.; Szczechowski N. (2004, 2004)
Title screen